Official Batch Control of Rabies Veterinary Vaccines: Current Situation and Perspectives in the European Union. Issue 1 (March 2013) - Servat, Alexandre; Cliquet, Florence
The use of seroneutralisation techniques is the first concrete step toward the replacement of the mouse challenge test and its derivatives for the batch testing of rabies vaccines